Distributed multiple tuned mass dampers for seismic response control in bridges. Issue 12 (7th January 2019) - Matin, Abdul; Elias, Said; Matsagar, Vasant
Abstract : The effectiveness of distributed multiple tuned mass dampers (d-MTMDs) in seismic response control of bridges was investigated. Numerical models were developed for evaluating the seismic response of concrete and steel truss bridges without and with tuned mass damper(s) (TMD(s)) installed. The modal frequencies and mode shapes of the uncontrolled and controlled bridges were used for suitable design and placement of the TMDs. Two horizontal components of earthquakes were simultaneously applied while duly considering the bi-directional interaction of the seismic response. The seismic response of the bridges was evaluated when all multiple tuned mass dampers (MTMDs) were installed at mid-span and when d-MTMDs were installed as per the modal properties. Coupled differential equations of motion of the bridges subjected to the bi-directional earthquake ground motions were derived and solved using the modified modal superposition method. Variations in pier base shear, support reaction, deck displacement and deck acceleration under real earthquake ground motions were computed to study the effectiveness of installing MTMDs and d-MTMDs. The results showed that d-MTMDs installed as per the modal properties of the bridges are effective in reducing the maximum pier base shear, support reaction, deck displacement and deck acceleration in both the longitudinal and transverse directions.